Worldwide estimates of incidence, prevalence and mortality of type 1 diabetes in children and adolescents: Results from the International Diabetes Federation Diabetes Atlas, 9th edition - Patterson, Christopher C.; Karuranga, Suvi; Salpea, Paraskevi; Saeedi, Pouya; Dahlquist, Gisela; Soltesz, Gyula; Ogle, Graham D. (Diabetes research and clinical practice, 2019)
This article describes the methods, results and limitations of the International Diabetes Federation (IDF) Diabetes Atlas 9th edition estimates of worldwide numbers of cases of type 1 diabetes in children and adolescents. Most information in the published literature is in the form of incidence rates derived from registers of newly-diagnosed cases. After systematic review of the published literature and recent conference abstracts, identified studies were quality graded. If no study was available, extrapolation was used to assign a country the rate from an adjacent country with similar characteristics. Estimates of incident cases were obtained by applying incidence rates to United Nations 2019 population estimates. Estimates of prevalent cases were derived from incidence rates after making allowance for higher mortality rates in less-developed countries. Incidence rates were available for 45% of countries (ranging from 6% in the sub-Saharan Africa region to 77% in the European region). Worldwide annual incidence estimates were 98,200 (128,900) new cases in the under 15 year (under 20 year) age-groups. Corresponding prevalence estimates were 600,900 (1,110,100) existing cases. Compared with estimates in earlier Atlas editions, numbers have increased in most IDF regions, reflecting incidence rate increases, but prevalence estimates have decreased in sub-Saharan Africa because allowance has been made for increased mortality in those with diabetes. Worldwide estimates of numbers of children and adolescents with type 1 diabetes continue to increase.